Prevalence and characteristics of multivitamin-multimineral (MVMM) use among Saudi populations in Riyadh, Saudi Arabia: A cross-sectional study. Issue 4 (28th January 2022) - Alwalan, Saleh I.; Alrasheed, Abdullah A.; Aldossari, Khaled K.; Al-Zahrani, Jamaan M.; Alshahrani, Abdullah Mohammed; Batais, Mohammed A.; Almigbal, Turky H.
Abstract : Abstract: Use of multivitamin multimineral (MVMM) preparations is prevalent and growing worldwide, contributing to major health expenditure. Minimal literature on prevalence and characteristics of MVMM use is available from Saudi Arabia. The study was conducted to determine the prevalence and characteristics of MVMM use among Saudi population in Riyadh, Saudi Arabia. A cross-sectional study was conducted at 6 shopping malls located in the different regions of Riyadh city for 6 months from February 01, 2019, to July 31, 2019. A well-structured English questionnaire was developed, translated into Arabic language, and validated by the experts. A pertinent inclusion and exclusion criteria were established. After having informed consent to be included in the study, the printed copies of the questionnaire were distributed among the participants using a convenient sampling technique. The data were collected and analyzed using SPSS version 24. Descriptive statistics were presented as numbers, percentages, means, and standard deviations. A P value of ≤.05 and 95% confidence intervals were used to report the statistical significance. Out of 1200 surveys distributed, 1105 were returned by the participants (response rate 92%). Prevalence of MVMM supplements use turned out to be 47%. The study revealed statistically significant association between MVMM use and gender, marital status, education, regular exercise, smoking, following special diet, and eating fruits and vegetables ( P  ≤ .05). Majority of the participants used MVMM on daily basis (57.9%), and hospital prescriptions (57.9%) were the most common reason of MVMM use. Majority of the participants used MVMM for diet supplements (32.2%), health promotion (29.4%), and treatment of disease (16%). The MVMM use is prevalent in Saudi population, warranting sound regulatory policies for their judicial use and increase awareness about the benefits and side effects of dietary supplements.